The curcumin-loaded zein-shellac nanoparticles using pH-driven method: Fabrication, characterization, and anti-inflammatory effect - Xinyi Lv; Zijian Wu; Limin Wang; Peibo Guo; Ao Qu; Wenjing Liang; Pengbo Zheng; Yuan Li; Wen Zhang (Journal of Functional Foods, 2025)
Curcumin (Cur), a naturally occurring flavonoid compound, is known for its multiple health benefits. Nevertheless, its bioavailability is greatly restricted due to poor solubility and stability. In order to address this problem, phytic acid was used in a pH-driven method to create curcumin-loaded zein-shellac nanoparticles (Zein-SH-CurNPs). The results confirmed that the hydrophobic center of zein-shellac nanoparticles (Zein-SHNPs) effectively encapsulated curcumin, leading to the formation of spherical particles that exhibited an impressive encapsulation efficiency of 96.96 % and a loading capacity of 4.65 %. Curcumin-induced zein fluorescence quenching was found to be static using fluorescence spectroscopy. In vivo colitis experiments conducted on mice disclosed that Zein-SH-CurNP exhibits a protective effect against DSS-induced colitis. Notably, the levels of pro-inflammatory cytokines, namely tumor necrosis factor-α (TNF-α), mouse interleukin-6 (IL-6), and interleukin-1β (IL-1β), were significantly reduced. To summarize, the results suggest that the zein-shellac composites hold potential as advanced nano-delivery structures for insoluble bioactive substances.